Pt-Sn alloy shells with tunable composition and structure on Au nanoparticles for boosting ethanol oxidation - Qian, Ningkang; Ji, Liang; Li, Xiao; Huang, Jingbo; Li, Junjie; Wu, Xingqiao; Yang, Deren; Zhang, Hui (Frontiers in Chemistry, 2022)
Combining the core-shell structure with the optimization of surface composition and structure in the shell is a fantastic strategy to enhance the electrocatalytic performances. Here, we synthesized trimetallic Au@PtxSny core-shell nanoparticles (NPs) with tunable composition and structure of Pt-Sn alloyed shells. Impressively, the Au@PtSn core-shell NPs with hexagonal PtSn alloyed shells exhibited the highest mass activity and specific activity toward ethanol oxidation reaction (EOR) in alkaline electrolyte, which are 13.0 and 12.7 times higher than those of the commercial Pt/C. In addition, the Au@PtSn core-shell NPs displayed the best stability compared to commercial Pt/C, with only 44.8% loss vs. 86.8% loss in mass activity after 1000 s due to the stronger anti-poisoning ability for reaction intermediates. The theory calculations reveal that the introduction of Au core and alloying Pt with Sn both endow Pt with an appropriate d-band center, and thus effectively boosting the EOR activity.